Reaction of Urinary Stones with Hydroxy Acids - Mahapatra (Chowdhury), Basabi; Bala, Shail (Asian Journal of Chemistry, 2010)
An attempt has been made to solubilise the insoluble ingredientsof the kidney stones (powdered stones and then whole stones) withplant acids (citric and malonic acids) and then by some fruit juices,e.g., tomato juice (which contains these plant acids) and also withextracts of some natural products, e.g., Kurthi (Dolichos bifluorus)containing inorganic and organic polyphosphates.